Perspectives on meaning in qualitative research - Noora J. Ronkainen; Michael McDougall (Bern Open Publishing, 2024)
A characterising trait of qualitative research, as opposed to quantitative research, is its assumed focus on meaning. For example, Smith and Sparkes (2016, p. 2) suggested that "To interpret phenomena in terms of the meanings people bring to them, qualitative researchers draw on a variety of empirical materials". Although there might be an intuitive understanding of what "meaning" means, different traditions of qualitative research have unique ways of conceptualising where meaning is located and how it might best be studied. In this presentation, we will explore three qualitative traditions - phenomenology, narrative inquiry and cultural analysis - to explicate these different assumptions and how they influence the qualitative research process. Firstly, we will focus on phenomenological approaches to qualitative research which often emphasise the lived, pre-verbal experience of meaning before it is crystallised into words. From this perspective, the challenge for the qualitative research is to help the participants to explicate meanings of their experience through careful questioning. Secondly, we explore narrative approaches that consider meaning as created through storytelling and co-constructed with the researcher with particular audiences in mind. From this perspective, meaning is personal, but constructed from the cultural building blocks of example stories that are available to the storyteller. Finally, in cultural analysis, the focus is not on personal meaning, but rather the culturally shared webs of significance that make meaningful actions possible for cultural insiders. We conclude that explicating the types of assumptions that researchers draw on in the study of meaning can enhance the quality of qualitative research, and that the diverse perspectives often lead to complementary, enriching understandings of meaning in the world of sport and physical culture. References Smith, B., & Sparkes, A. C. (Eds.). (2016). Routledge Handbook of Qualitative Research in Sport and Exercise. Routledge.